The PlayStation dreamworld - Bown, Alfie (Theory redux, 2018)
"From mobile phones to consoles, tablets and PCs, we are now a generation of gamers. The PlayStation Dreamworld is--to borrow a phrase from Slavoj Zizek--the pervert's guide to videogames. It argues that we can only understand the world of videogames via Lacanian dream analysis. It also argues that the Left needs to work inside this dreamspace – a powerful arena for constructing our desires – or else the dreamworld will fall entirely into the hands of dominant and reactionary forces. While cyberspace is increasingly dominated by corporate organization, gaming, at its most subversive, can nevertheless produce radical forms of enjoyment which threaten the capitalist norms that are created and endlessly repeated in our daily relationships with mobile phones, videogames, computers and other forms of technological entertainment. Far from being a book solely for dedicated gamers, this book dissects the structure of our relationships to all technological entertainment at a time when entertainment has become ubiquitous. We can no longer escape our fantasies but rather live inside their digital reality"--Provided by publisher.